Análise da variação espaço-temporal dos parâmetros para a modelagem estocástica da precipitação pluvial diária no Rio Grande do Sul - Calgaro, Marcelo (2006)
Rio Grande do Sul is one of the largest grains producers State of the Country and except for some cultures produced under irrigation, most cultures are led in not irrigated systems, what they do them extremely dependent of the weather conditions and especially to the rainfall. In consequence of this dependence and in virtue of this variable to be so important, several studies have been being developed in the attempt to characterize the space behavior and temporal bone of the pluvials precipitations in the State. Thus the goal of this work was to study the space variation and temporal bone of the alpha parameters and beta of the range function for the generation of daily pluvial precipitation in Rio Grande do Sul State. The daily rainfall data used in this work were obtained from different weather station of the State through to National Agency of Waters (ANA). The modeling of the daily precipitation was divided into two stages, firstly with the modeling of the occurrence of the daily pluvial precipitation and afterwards the modeling of the quantity of daily pluvial precipitation. It accomplished the estimate of the alpha parameters and beta of the range function from the historical series, followed by the adjustment of these parameters in function of time and of the space and afterwards the comparison among values estimate for mathematical models and the values observed in the data of the used stations. According to the proposed methodology and with the obtained results can conclude that the elements of the transition head office and the alpha parameters and beta introduced variability regarding time and the geographical position of the station and were modelled to represent this variability. The mathematical functions obtained, allow estimating the matrix transition elements and the gamma probability parameters from historical daily rainfall data in Rio Grande do Sul State weather station. The developed methodology can be applied to generate daily rainfall series from different weather stations of Rio Grande do Sul State, and the unpublished character of work was the obtainment of the necessary parameters in function of the geographical coordinates of the station of analytic way.